2017
DOI: 10.1037/xlm0000364
|View full text |Cite
|
Sign up to set email alerts
|

A goal bias in action: The boundaries adults perceive in events align with sites of actor intent.

Abstract: We live in a dynamic world comprised of continuous events. Remembering our past and predicting future events, however, requires that we segment these ongoing streams of information in a consistent manner. How is this segmentation achieved? This research examines whether the boundaries adults perceive in events, such as the Olympic figure skating routine used in these studies, align with the beginnings (sources) and endings (goals) of human goal-directed actions. Study 1 showed that a group of experts, given an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
53
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(59 citation statements)
references
References 53 publications
3
53
1
Order By: Relevance
“…Moreover, amateur dancers perceived fewer events in the dance phrase less after they were familiarized with it. Likewise, Levine, Hirsh-Pasek, Pace, and Michnick Golinkoff (2017) asked experts and novices to segment an Olympic figure-skating routine and found that experts perceived fewer, longer events.…”
Section: What Factors Influence Event Segmentation?mentioning
confidence: 99%
“…Moreover, amateur dancers perceived fewer events in the dance phrase less after they were familiarized with it. Likewise, Levine, Hirsh-Pasek, Pace, and Michnick Golinkoff (2017) asked experts and novices to segment an Olympic figure-skating routine and found that experts perceived fewer, longer events.…”
Section: What Factors Influence Event Segmentation?mentioning
confidence: 99%
“…These findings suggest that movement information has less influence on adults’ segmentation boundary judgments for events involving goal structures than events lacking those higher‐level structures. Further, for a skilled motion event such as figure skating, experts’ segmentations are more sensitive to the goal structure of the event than novices’ segmentations (Levine et al, ; see also Bläsing, ). That is, having more top‐down information about actors’ goals alters adults’ interpretation of low‐level perceptual cues.…”
Section: Adults: Leveraging Event Predictions For Segmentationmentioning
confidence: 99%
“…Moreover, given the redundancy between movement features and goal structures in events (Zacks et al, )—particularly for everyday events—one possibility is that infants may initially be sensitive to low‐level event structure (i.e., action regularities, movement features), and may gradually learn about the goal structure of events through the overlap of these structures (Baldwin et al, ). Additionally, infants’ burgeoning understanding of actors’ goals may facilitate infants’ ability to segment events, and infants’ event segmentation may become more sophisticated as their understanding of goal‐directed action matures through event experience, just as expertise in adults leads to greater alignment of segmentation patterns with event goal structure (Levine et al, ). These possibilities are explored as we turn to the evidence for mechanisms of event segmentation in children.…”
Section: Adults: Leveraging Event Predictions For Segmentationmentioning
confidence: 99%
See 1 more Smart Citation
“…Further, experts segmented the same dance sequence even less after physically embodying, learning, and performing it. Levine and colleagues [ 18 ] replicated these findings among expert figure skaters, and clarified that visual familiarity among novice observers does not replicate the effects of physical expertise.…”
Section: Introductionmentioning
confidence: 99%